POTENSI DAN ANALISIS TEKNO-EKONOMI EKSTRAK TANAMAN SEBAGAI GREEN INHIBITOR PADA BAJA KARBON - Yeni Nurahmawati, - (2020)
Carbon steel is used in industrial applications, but the performance of carbon steels can be affected by corrosion attacks in corrosive solutions. Therefore, to reduce the rate of corrosion added corrosion inhibitors that are environmentally friendly and the price is relatively cheap. Plants have potential as corrosion inhibitors because they contain N, S, P, O atoms and have PEB bonds. The purpose of this study was to determine the extraction method, active compounds, the potential of plant extracts, inhibition mechanism, engineering evaluation and economic evaluation of the production of corrosion inhibitor solution. Literature study was conducted with a narrative study model of 54 articles related to the potential of plant extracts as carbon steel corrosion inhibitors in corrosive media sourced from Elsevier, Springer, Wiley, Taylor & Francis and Heliyon in the period 2019-2020. The keywords used are plant extract, corrosion inhibitor, carbon steel, and corrosive medium. Economic evaluation is carried out with several parameters such as: GPM (Gross Profit Margin), PBP (Payback Period), and CNPV (Cumulative net present value) which is based on simple mathematical calculations using Microsoft Excel applications. From the review article analysis it was found that the extraction method used was the reflux method, plant extracts containing flavonoid compounds, saponins, tannins, alkaloids and terpenoids, the efficiency of inhibition was in the range of 55.62% - 99.92%, and the mechanism of inhibition took place spontaneously , physorption, exothermic, following langmuir isotherms and the types of inhibitors used are mixed. From the project feasibility test it was found that the project suffered a loss if the tax paid was more than 50% and the selling price and production capacity were less than 90%. The project can produce 271350 L / year corrosion inhibitor solution. Production of a corrosion inhibitor solution can provide up to 96% profit. Economic evaluations show positive results because the payback period (PBP) occurs around the 5th year, and profits will continue to increase until the 20th year. Thus, the production of a corrosion inhibitor solution can be considered a profitable project.